New developments in feeding wheat to cattle - J. Brethour; B. Lee; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1985)
At least for the varieties we studied, hard red winter wheat was superior to soft red winter wheat in beef cattle rations. That contradicts the perception that feed wheats should be soft. The net energy values of Larned hard wheat and Hart soft wheat were 102% and 99% that of corn, respectively. Adding Rumensin® to wheat rations improved performance, probably by reducing acidosis instead of increasing ration net energy value. There was a positive associative effect when wheat and milo were fed together but not when wheat and corn or corn and milo were combined. Steer performance was improved by adding 3% fat to rations; that improvement was proportional to the amount of wheat in the rations and was probably due to the fat's added energy, Steers that were fed fat graded better and gained more uniformly. When 100% wheat was fed, overall performance was satisfactory only when fat was included.
Keywords: Cattlemen& #x27; s Day; 1985; Kansas Agricultural Experiment Station contribution; no. 85-319-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 470; https://krex.k-state.edu/dspace/handle/2097/6905